POST-FORDISM AND INCORPORATED DISPOSITIONS. FROM A SITUATIONAL ANALYSIS, TO A STRUCTURALCONSTRUCTIVIST THEORY - Muzzioli, Simone Michelangelo (European Scientific Journal, ESJ, 2014)
What we propose is to build a social analysis in order to bring out those structured and structuring dispositions culturally embedded in individual habitus through those distinction devices objectified by the conditional and selective policies of labour market and welfare state. These dispositions can be read as symbolic and cultural obstacles to the idea of an unconditional and universal basic income. So, we suppose that the typical conditional and selective fordist-matrix of welfare and labour policies contributes strongly to the generation of individual narrow-minded and depending habitus, in the bourdieusian sense, which are today in open contradiction with the new flexible and open-minded post-Fordist habitus. A contradiction manifested by nowadays socio-economic problems and welfare hardship. Thus, starting from the findings of a previous Situational Analysis, we acknowledges the paradigmatic changes occurred in our capitalist system. In turn, this acknowledgements has led us toward a critical review of welfare policies marketization, which is more and more grounded on the principles of conditionality and selectivity. So we suggest to undertake a research in which the operationalization of the heuristic concept of a universal and unconditional basic income will take place through the breaking of social actors' mental and dispositional frameworks. Indeed, actors will be analytically classified according to their own configuration of capitals, social and axiological position. Moreover, thanks to an integrated qualitative/quantitative approach, the intent is to show how the mainstream architecture of contemporary welfare state and labour policies, based on the principles of selectivity and conditionality, contributes paradoxically to the generation of those social distinctions and problems that instead wants to oppose (excessive state aid, dependency, emancipatory constraints, exclusion, stigmatization, profiteering etc.).